1995
DOI: 10.1007/s004410050506
|View full text |Cite
|
Sign up to set email alerts
|

Numerous cell targets for gastrin in the guinea pig stomach revealed by gastrin/CCK B receptor localization

Abstract: The localization of the gastrin/CCKB receptor (GR) has recently become a subject of debate, especially since the publication of evidence for its presence in an unsuspected location, namely in the lamina propria, the submucosal layer of the stomach lining. Knowledge of the receptor localization is important because of the critical role of gastrin secretion and its trophic effects on the gastric epithelium. The present study, which utilizes immunohistochemistry and electron microscopy as primary tools, provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…For example, they showed less binding to pit cell-specific CTB lectin, although the pit region was extensively elongated. In previous studies, CCKB-Rs were localized in parietal, chief, and ECL cells (28,41). Thus the CCKB-R-positive cells in the lower glands in control mice appear to be a mixture of these cells.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…For example, they showed less binding to pit cell-specific CTB lectin, although the pit region was extensively elongated. In previous studies, CCKB-Rs were localized in parietal, chief, and ECL cells (28,41). Thus the CCKB-R-positive cells in the lower glands in control mice appear to be a mixture of these cells.…”
Section: Discussionmentioning
confidence: 63%
“…CCKA-Rs exhibit a 500-to 1,000-fold higher affinity for sulfated analogs of CCK than for gastrin, whereas CCKB-Rs have approximately equal affinity for both sulfated and non-sulfated peptide analogs of CCK and gastrin (32,34,46,47). CCKB-Rs are present in parietal, ECL, and probably somatostatin cells (2,4,23,27,28,41 (2,28). Immunohistochemical studies have also demonstrated the distribution of CCKB-R in the same cell types (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Binding and functional studies demonstrated that both CCK1R and CCK2R are present on guinea pig chief cells (91, 389). In addition to detection on parietal and chief cells in the guinea pig stomach, CCK2R was also detected on rare unidentified endocrine cells that were negative for gastrin, histamine, secretin, somatostatin, enkephalin, and gastrin-releasing peptide (521). Precise cellular localization of human stomach CCK2R by in situ RT-PCR and immunohistochemistry demonstrated expression in gastric parietal, ECL, and putative precursor cells (261,451).…”
Section: Stomachmentioning
confidence: 92%
“…Tumors grown in athymic mice were trimmed to pieces not more than 0.5 cm in each dimension and fixed in 4% formaldehyde in PBS for 16 h at 4°C. Fixed specimens were processed to sections and stained with rabbit polyclonal antibodies to CCKBR as described (34).…”
Section: Methodsmentioning
confidence: 99%